Web-Based Donation Information System At Tpq / Tqa Masjid Nurhikmah Kampung Melayu Nanggalo Padang - M. ILHAM A. SIREGAR, M. ILHAM A. SIREGAR; AGUS SUTARDJO, AGUS SUTARDJO; rafi12, Rizki Muhammas Rafi (Jurnal Manajemen Teknologi Informatika, 2023)
Nurhikmah Mosque is a mosque located in Kampung Melayu Nanggalo Padang. This research is motivated by the problem of the Nurhikmah Mosque, which currently does not have an information system for managing donations. The large number of donors must come directly to the Nurhikmah Mosque, so it takes time to get to the location of the mosque, if the donor is far from the location of the Nurhikmah Mosque. To overcome this problem, a management system is needed that can be accessed easily by the community. The research conducted in this final project is to create and design a web-based donation information system for the Nurhikmah Mosque. This information system is made with Hypertext Preprocessor (PHP), CodeIgniter Framework and MySQL database. The research method used is waterfall. Starting with system analysis, design, coding and the final stage is system testing. The purpose of this system that will be created is to make it easier for the wider community to make donations/charity to the Nurhikmah Mosque.